2021
DOI: 10.2967/jnumed.120.261032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Deep Learning–Based Approaches to Segment Bowel Air Pockets and Generate Pelvic Attenuation Maps from CAIPIRINHA-Accelerated Dixon MR Images

Abstract: Attenuation correction (AC) remains a challenge in pelvis PET/MR imaging. In addition to the segmentation/model-based approaches, deep learning methods have shown promise in synthesizing accurate pelvis attenuation maps (μ-maps). However, these methods often misclassify air pockets in the digestive tract, which can introduce bias in the reconstructed PET images. The aims of this work were to develop deep learning-based methods to automatically segment air pockets and generate pseudo-CT images from CAIPIRINHA-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The use of deep learning-based methods in PET attenuation correction has been increasingly popular, particularly in PET/MRI imaging where lack of CT-based attenuation maps introduced significant challenges to accurate PET quantification [45]. In previous work, CNNs were trained using coregistered MR and CT images to generate pseudo-CT based µ-maps for head [46,47] and pelvis [48][49][50], which were shown to be more accurate compared to vendor-provided atlas based µ-maps. Besides, the use of supervised deep learning techniques such as CNN has limited performance in generating whole-body µ-maps as these techniques require perfectly aligned MR and CT whole-body images which is not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…The use of deep learning-based methods in PET attenuation correction has been increasingly popular, particularly in PET/MRI imaging where lack of CT-based attenuation maps introduced significant challenges to accurate PET quantification [45]. In previous work, CNNs were trained using coregistered MR and CT images to generate pseudo-CT based µ-maps for head [46,47] and pelvis [48][49][50], which were shown to be more accurate compared to vendor-provided atlas based µ-maps. Besides, the use of supervised deep learning techniques such as CNN has limited performance in generating whole-body µ-maps as these techniques require perfectly aligned MR and CT whole-body images which is not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge in this case is to accurately identify the bone which is where most MR-based techniques are prone to error. A number of methods which used paired 2D Dixon and CT [ 241 , 242 ], 3D ZTE and CT [ 40 ], 3D T 1 and CT [ 243 ] images or an additional deep learning-based segmentation step to segment the air from the bowl areas [ 244 ], resulted in comparable biases of approximately 5% in the pelvic bone regions. Moreover, it was recently shown that if the uncertainty in the prediction is also taken into account, implants could be more easily identified [ 245 , 246 ].…”
Section: Machine Learning Attenuation Correction Methodsmentioning
confidence: 99%
“…The main challenge of these approaches was that neglecting air pockets in the pelvis AC maps could lead to inaccuracies in reconstructed PET images. However, these innovative methods based on CNNs even showed the capability of predicting air pockets and include them in the AC maps [103].…”
Section: Attenuation Correctionmentioning
confidence: 99%